Strict liability versus policy and regulation for environmental protection and agricultural waste management in Malaysia - Ishak, Mohd. Bakri; Abu Samah, Mohd Armi (Thai Society of Higher Eduction Institutes on Environment, 2010)
Basically, strict liability is part of the mechanism for expressing judgment or sentence by using direct evidence. This principle is very useful in order to obtain remedies from any damage either directly or indirectly. The principle in Rylands v Fletcher is responsible on imposing strict liability where if something brought onto land or collected there escapes liability under this rule can include not only the owner of land but also those who control or occupation on it. However, as a matter of fact, policy and regulation are also important in taking any action against any party who are responsible for environmental pollution or damage, which may include mismanagement of waste or industrial waste or agricultural waste. There are certain policies and regulations on environmental protection such as the National Environmental Policy, certain Acts and several regulations under the Environmental Quality Act 1974 (Act 127), which are very useful for agricultural waste management inter alia: Waters Act 1920 (Act 418), Environmental Quality (Prescribed Premises) (Crude Palm Oil) Regulations 1977, Environmental Quality (Prescribed Premises) (Raw Natural Rubber) Regulations 1978, Environmental Quality (Sewage and Industrial Effluents) Regulations 1979, and Environmental Quality (Compounding of Offences) Rules 1978. As a matter of fact, we should realize that time is of an essence for any parties which are involved in court cases and especially in avoiding the element of externality, which is commonly suffered by the government. In making this paper, therefore, some element of comparison with certain developed jurisdiction such as in the United Kingdom and Japan could not be avoided in order to obtain better outcome and to be more practical for the purpose of environmental protection and agricultural waste management.